Calibration of a thermoluminescent dosimeter worn over lead aprons in fluoroscopy guided procedures. (28th March 2018) - Quintero-Quintero, A; Patiño-Camargo, G; Soriano, Á; Palma, J D; Vilar-Palop, J; Pujades, M C; Llorca-Domaica, N; Ballester, F; Vijande, J; Candela-Juan, C
Abstract: Fluoroscopy guided interventional procedures provide remarkable benefits to patients. However, medical staff working near the scattered radiation field may be exposed to high cumulative equivalent doses, thus requiring shielding devices such as lead aprons and thyroid collars. In this situation, it remains an acceptable practice to derive equivalent doses to the eye lenses or other unprotected soft tissues with a dosimeter placed above these protective devices. Nevertheless, the radiation backscattered by the lead shield differs from that generated during dosimeter calibration with a water phantom. In this study, a passive personal thermoluminescent dosimeter (TLD) was modelled by means of the Monte Carlo (MC) code Penelope. The results obtained were validated against measurements performed in reference conditions in a secondary standard dosimetry laboratory. Next, the MC model was used to evaluate the backscatter correction factor needed for the case where the dosimeter is worn over a lead shield to estimate the personal equivalent dose H p (0.07) to unprotected soft tissues. For this purpose, the TLD was irradiated over a water slab phantom with a photon beam representative of the result of a fluoroscopy beam scattered by a patient. Incident beam angles of 0° and 60°, and lead thicknesses between the TLD and phantom of 0.25 and 0.5 mm Pb were considered. A backscatter correction factor of 1.23 (independent of lead thickness) was calculated comparing the results with those faced in reference conditions (i.e., without lead shield and with an angular incidence of 0°). The corrected dose algorithm was validated in laboratory conditions with dosimeters irradiated over a thyroid collar and angular incidences of 0°, 40° and 60°, as well as with dosimeters worn by interventional radiologists and cardiologists. The corrected dose algorithm provides a better approach to estimate the equivalent dose to unprotected soft tissues such as eye lenses. Dosimeters that are not shielded from backscatter radiation might underestimate personal equivalent doses when worn over a lead apron and, therefore, should be specifically characterized for this purpose.